2019
DOI: 10.1002/er.5022
|View full text |Cite
|
Sign up to set email alerts
|

Effect of charge rate on capacity degradation of LiFePO 4 power battery at low temperature

Abstract: Summary Limited by the current power battery technology, electric vehicles show extremely poor duration performance and potential risk at low temperature, which is mainly caused by poor charging performance of lithium‐ion batteries. To explore the impact of charging process on cycle degradation at low temperatures, a cycle aging experimental scheme with different charging C‐rate (0.3C and 0.5C) under −10°C and −20°C was designed for the commercial LiFePO4 battery. The experimental batteries showed severe degra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 41 publications
0
19
0
Order By: Relevance
“…The reduction and uneven deposition of lithium ions on the lithium electrode surface during charge and discharge cycles lead to the formation and growth of lithium dendrites, which destabilize the SEI film and lead to shortened battery life, reduced coulombic efficiency, and safety hazards, such as puncturing the diaphragm, leading to a short circuit. The simulated lithium dendrite image (Figure ) shows that the growth rate of lithium dendrites is positively correlated with the magnitude of the charge/discharge current, and the potential gradually increases with the growth of dendrites. To investigate the hazards of dendrites piercing the diaphragm as a result of the large amount of lithium deposited during the reaction, Wu et al designed an experimental scheme for cyclic aging of commercial LFP batteries at different charging rates (0.3 and 0.5 C) at low temperatures. During the experiments, it was found that the cathode aging was mainly caused by lithium metal deposition during the low-temperature charge/discharge cycles.…”
Section: Structural Characteristics and Defects Of Lfpmentioning
confidence: 99%
“…The reduction and uneven deposition of lithium ions on the lithium electrode surface during charge and discharge cycles lead to the formation and growth of lithium dendrites, which destabilize the SEI film and lead to shortened battery life, reduced coulombic efficiency, and safety hazards, such as puncturing the diaphragm, leading to a short circuit. The simulated lithium dendrite image (Figure ) shows that the growth rate of lithium dendrites is positively correlated with the magnitude of the charge/discharge current, and the potential gradually increases with the growth of dendrites. To investigate the hazards of dendrites piercing the diaphragm as a result of the large amount of lithium deposited during the reaction, Wu et al designed an experimental scheme for cyclic aging of commercial LFP batteries at different charging rates (0.3 and 0.5 C) at low temperatures. During the experiments, it was found that the cathode aging was mainly caused by lithium metal deposition during the low-temperature charge/discharge cycles.…”
Section: Structural Characteristics and Defects Of Lfpmentioning
confidence: 99%
“…[150] ) and illustrate the increase in plating rate at lower temperatures, consistent with experimental studies. [45,63,93,[154][155][156][157][158] Choe has applied this reduced order model to investigate degradation with the intent of mitigating aging and Li plating due to fast charging. [140,[150][151][152][159][160][161][162][163] This type of approach could be utilized in a battery management system or charge controller to avoid Li plating completely, or to allow for a quantifiable amount of Li plating that could be electrochemically removed later.…”
Section: Plating Modelingmentioning
confidence: 99%
“…Wu et al explored the effect of charge rate on capacity degradation at low temperatures, but the C‐rates used in this study did not meet the requirement of fast charging processes. [ 18 ] In a recent study, Lopez et al studied the effect of conditioning protocols on the performance of a commercially available lithium‐ion battery to show the optimum procedure affecting the formation process. [ 19 ] The effects of SOC, temperature, and duration were investigated during the protocols in which the level of a single control factor varied.…”
Section: Introductionmentioning
confidence: 99%